Corruption Crime In Internet Network Procurement At Sultan Syarif Kasim State Islamic University In Pekanbaru, Riau - Mariyam Indayani; Hartoyo Hartoyo (Fakultas Hukum Dehasen, 2024)
Procurement of goods and services is the procurement of goods/services financed by the APBN/APBD. In the legal case in case number 57/Pid.Sus-TPK/2022/PN Pbr is a case of procurement of goods and services in the procurement of internet networks at Sultan Syarif Kasim Riau State Islamic University. In this case, there was corruption in the form of gratification where there was abuse of office and bribery in the procurement of the internet network at Sultan Syarif Kasim State Islamic University. The problems discussed are how the system for procuring goods and services in the internet network at the Sultan Syarif Kasim State Islamic University in Pekanbaru Riau City and how the judge's considerations in passing the defendant's decision in case number 57/Pid.SUS-TPK/2022/PN Pbr. The author uses the normative writing method which aims to collect written legal material sources by reviewing previous laws and publications. With the results of the discussion, namely the procurement of goods and services has been regulated in such a way and also the judge's decision which only focuses on Law Number 28 of 1999 concerning the Implementation of a State that is Clean and Free from Corruption, Collusion and Nepotism and Law Number 16 of 2018 concerning Procurement of Goods / Government services, but did not try to look at article 12b of Law Number 21 of 2001 concerning Amendments to Law Number 31 of 1999 concerning Eradication of Corruption Crimes.